Guided Imagery Using Classical Music on The Reduction in Pain Level of Fracture Patients - Candra Kusuma Negara; Akhmad Murjani; Anna Martiana; Fajar Kurniawan (Asosiasi Institusi Pendidikan Ners Indonesia (AIPNI), 2019)
Introduction: Fracture is the medical term for a broken bone. Fractures are common; the average person has two during a lifetime. One of the Intervention on handling the case of fracture is surgical operation. Method of handling the pain that can be done is the non-pharmacological techniques that provide guided imagery through the use of classical music. The purpose of this study to understand the effect of guided imagery utilizing classical music to decrease the scale of pain on post fracture surgery. Methods: The study was quasi-experimental pre-test and post-test group approach The sampling technique employed was accidental sampling with the total of 22 respondents. The guided therapy image uses classical music with an intensity of 60-80 dB and a volume of 40-50% for +/- 20 minutes. The data collection tool utilized was VAS (Visual Analog Scale) observation sheets. The data analysis utilized was Wilcoxon Sign Rank Test. Results: The result of statistical analysis of Wilcoxon Signed Rank Test obtained p value = 0.000 with significance level <0.05, it was found that there was an effect of giving classical music therapy to a decrease in the pain scale of post-fracture patients. Musical intervention was associated with a significant decrease in heart rate, improvement in oxygen saturation, and reduction in the perception of paint. Conclusions: There was an influence upon the use of guided imagery utilizing classical music towards the decreasing scale of pain on post fracture surgery.